Perception on muslim women as judges in the courts in modern context: a critical study of the views of Muslim scholars - Ali, Md. Yousuf (IIUM Press, 2011)
The appointment of women as judges in Muslim countries remains a challenging and debatable issue due to a general perception that such appointment might not be in conformity with the Shari'ah. Dual legal systems, i.e. civil and Shari'ah courts exist in the Muslim world. The Shari'ah Court has jurisdiction only over persons who are Muslims and its jurisdiction is only in the area of family law, not in criminal law. A few Muslim women, even though their growth is continuously increasing, are contributing as judges in the judicial system in the Muslim world. However, there is no sacred text that directly allows women to be appointed as judges in courts. The issue of female judgeship is still disputable and contestable. In the modern context, it is imperatively essential to exercise ijtihad on the basis of the textual sources in order to make a clear stance regarding the permissibility of the appointment of a female judge and the prohibition ofher appointment in the courts. These juristic interpretations of several textual sources would benefit the Muslim Ummah in particular and the entire humanity in general. It is also argued that if the avenues of opportunities are given to women, they would be able to contribute in the judicial system like other sectors. Therefore, this paper aims to critically evaluate the perception on Muslim women as judges in the contemporary judicial system in accordance with the views of both the classical and contemporary Islamic scholars towards a better understanding of the role of women as judges in the civil courts and the Shari'ah courts who carry out the stance of the Islamic legal system on the basis of the textual arguments of the Qur'an and the Sunnah. In particular, it intends to focus on: a) analyzing the concept, the prohibition and permissibility of the appointment of women as judges from the Islamic legal perspective, b) determining the Islamic stance of its validity and non-validity in the modern context in order to benefit from their services, c) evaluating critically and clarifying the negative perceptions and misunderstandings of the issue from the Islamic perspective and, most importantly, d) providing some recommendations and the Shari'ah-based principles that can illuminate the existing debate in Muslim society about womens judgeship in the Shari'ah as well as civil courts. This study also intends to outline a brief history of womens contribution in the judicial system. The following three key issues will be critically examined. The first concerns the question of the qualification of women to be judges, the second concerns the question of men s authority over women, the third concerns the legal stance ofthe Shari'ah about the appointment of Muslim women as judges in all courts with some recommendations and suggestions. Discussion would include implications of the research findings, shortcomings of the current study, and directions for future research.